Sleep and chronotype influence aerobic performance in young soccer players - Ciorciari, Andrea; Mulè, Antonino; Castelli, Lucia; Galasso, Letizia; Esposito, Fabio; Roveda, Eliana; Montaruli, Angela (Frontiers in Physiology, 2023)
People can be classified into three chronotypes (CT): Morning-type (M-type), Neither-type (N-type) and Evening-type (E-type). M-types perform better in the morning, E-types in the evening. It seems that bad sleep worsens physical performance. The impact of sleep and CT on specific sports and populations is unclear. Therefore, we wanted to assess agility, strength and endurance in young soccer players in relation to their sleep and chronotype. 58 players (13-19 years) were recruited. Sleep and CT were assessed by questionnaires. The physical trial was performed at 8:30 a.m. and 6:00 p.m., and included three tests to determine agility, strength and endurance. The sample was classified by CT as M-types (n=11), N-types (n=29) and E-types (n=18). Furthermore, they were categorized as people with Good Sleep/Wake quality (GSW, n=28) and people with Bad Sleep/Wake quality (BSW, n=30). Comparing the three CTs in the aerobic test, M-types performed better in the morning (p=0.01), while E-types in the evening (p<0.001). GSW performed better than BSW (p=0.019) in the aerobic test in the p.m. session. These results underline the difference in aerobic power between M- and E-types during the morning and evening session; moreover, they show a difference in p.m. aerobic performance according to sleep quality.